2011
DOI: 10.1590/s0102-695x2011005000093
|View full text |Cite
|
Sign up to set email alerts
|

Multiple emulsions containing amazon oil: açaí oil (Euterpe oleracea)

Abstract: Abstract:The aim of this work was to formulate O/W/O multiple emulsions containing açaí oil as a model system and to evaluate their physical stability and in vivo Sun Protection Factor (SPF). Multiple emulsions are complex dispersion systems, known also as, "emulsions of emulsions". These emulsion systems, have significant potential in the cosmetic industry. Euterpe oleracea Mart., Arecaceae, popularly known in Brazil as "açaí", is an economically important plant. Açaí oil has been used as antioxidant and as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
1
21
0
3
Order By: Relevance
“…Ferrari and Rocha-Filho (2011) demonstrated that the association between the polymeric surfactants and rheology modifier improved the stabilization of emulsion on the centrifugation test. According to Tadros (2004) the absence of rheology modifier in the formulations resulted in phase separation after centrifugation because there was an insufficient increase in the viscosity of the external phase of the vehicles to maintain the integrity of the emulsions.…”
Section: Preliminary Stability Testsmentioning
confidence: 97%
See 4 more Smart Citations
“…Ferrari and Rocha-Filho (2011) demonstrated that the association between the polymeric surfactants and rheology modifier improved the stabilization of emulsion on the centrifugation test. According to Tadros (2004) the absence of rheology modifier in the formulations resulted in phase separation after centrifugation because there was an insufficient increase in the viscosity of the external phase of the vehicles to maintain the integrity of the emulsions.…”
Section: Preliminary Stability Testsmentioning
confidence: 97%
“…at room temperature . The appearance, homogeneity and organoleptic characteristics were evaluated by macroscopic analyses (Ferrari, Rocha-Filho, 2011).…”
Section: Preliminary Stability Testsmentioning
confidence: 99%
See 3 more Smart Citations